Exploring Familiarity with and Use of CAT Technologies among Undergraduate Translation Students in Oman: The Case of Sultan Qaboos University - EL-Karnichi, Fouad; Al-Sharafi, Abdul Gabbar; Jamoussi, Rafik (Forum for Linguistic Studies, 2025)
Translation is becoming increasingly technology-dependent, with Computer-Assisted Translation (CAT) technology becoming more prevalent in supporting translators and interpreters. These tools are specifically designed to improve productivity, efficiency, and consistency of the translation process. This study aims to investigate the level of familiarity with and use of CAT technologies among BA undergraduate translation students at Sultan Qaboos University in Oman. A survey was conducted using a five-point Likert scale to evaluate students' familiarity with and use of CAT tools. The data collected were analyzed using descriptive statistics and frequency analysis. Cronbach’s Alpha was calculated to ensure the reliability and validity of the data. The findings of this research demonstrate an elevated level of familiarity with and use of CAT tools among the study sample. This study offers valuable insights into one of the most rapidly changing aspects of translation education, i.e., translation technologies. The study highlights the relevance of these findings for similar educational contexts, emphasizing the need for integrating CAT tools into translation curricula to improve the output of translators.